Economic consequences of the phenomenon of uberization on the example of the services of selected carriers in the transport industry - Stępnicka, Nina; Monastyrskyi, Grygorii; Sadowska, Beata; Walasek, Robert; Wiączek, Paulina; Zimon, Grzegorz (Technological and Economic Development of Economy, 2025)
Uberization is a process, phenomenon, trend, and direction that emerged in the 21st century economy thanks to Uber Technologies, Inc., which was the first to introduce a mobile application that connects drivers and passengers. Although the name of the trend was not formalized by the Uber corporation, it appeared a few years later to describe certain dependencies that emerged in the economy and that gained importance not only in the field of transportation services, but also in the field of finance, in the labor market, or in relation to the real estate market. The purpose of the study was to determine the impact of the progressive phenomenon of uberization on the competitiveness of the transportation industry in the pre-pandemic period and in the post-pandemic period. The study assumed the hypothesis that carpooling services, which are one of the important models of uberization, implemented in Poland through the BlaBlaCar app, can be a significant competitor to transportation services provided through traditional forms and models of communication, i.e., train and bus connections. The results of the study showed that BlaBlaCar services are a cheaper alternative to other means of transportation, i.e., public transport (Polskie Koleje Państwowe, PKP Intercity) and bus connections, although not always. As a rule, their competitiveness is higher for those routes and trips where there are many drivers offering free space in the car. On the other hand, on the routes less frequently visited by BlaBlaCar drivers, fares with a BlaBlaCar driver are higher than rail and bus fares. The considerations of the article meet the objectives of the cognitive goal and the application goal and showed that uberization in the transport industry is a significant phenomenon that is still developing and, in the future, may threaten traditional forms of transport, i.e., rail and bus travel.